Thickness of macular inner retinal layers and peripapillary retinal nerve fibre layer in neuromyelitis optica spectrum optic neuritis and isolated optic neuritis with one episode. Issue 6 (24th October 2016) - Peng, Chunxia; Wang, Wei; Xu, Quangang; Yang, Mo; Zhou, Huangfen; Zhao, Shuo; Wei, Shihui
Abstract: Purpose: The aim of this study was to evaluate the differences between macular inner retinal layers and peripapillary retinal nerve fibre layer (pRNFL) thickness in Chinese patients with neuromyelitis spectrum optic neuritis (NMOSD‐ON) and isolated optic neuritis (ION) with only one episode. Methods: This cross‐sectional study included 35 patients (35 eyes) with NMOSD‐ON (NMO‐IgG seropositive) and 46 patients (46 eyes) with ION after one episode. Spectral domain optical coherence tomography (SD‐OCT) was used to quantify pRNFL, macular RNFL (mRNFL), ganglion cell and inner plexiform layers (GCIPL) and inner nuclear layer (INL) thickness using an automated algorithm. Differences in OCT parameters between NMOSD‐ON and ION were compared after adjusting for age, sex and disease duration. Results: The pRNFL and mRNFL in some locations (average pRNFL, nasal pRNFL, nasal inferior (NI) pRNFL, nasal/temporal (N/T) ratio pRNFL, average mRNFL, inner temporal mRNFL, outer nasal mRNFL and outer temporal mRNFL) in NMOSD‐ON differed significantly from those in ION (all p   <   0.05). These parameters had moderate diagnostic accuracy, with area under curves (AUCs) ranging from 0.684 to 0.762 for pRNFL and from 0.660 to 0.700 for mRNF. The thickness of GC‐IPL and INL in all sectors was similar in NMOSD‐ON and ION (p   >   0.05). This study and our meta‐analysis of four previous studies obtained consistent results, with pooled mean difference (MD) −10.4  μ m (95% CI: −12.4 to −8.4, p   <   0.001) for pRNFL, −1.5  μ m (95% CI: −3.5 to 0.6, p   =   0.158) for mRNFL and 0.2  μ m (95% CI: −0.4 to 0.9, p   =   0.490) for GC‐IPL, respectively. Conclusions: Neuromyelitis spectrum optic neuritis (NMOSD‐ON) patients had more pRNFL and mRNFL loss compared to ION patients after one episode. Spectral domain optical coherence tomography (SD‐OCT) may help to distinguish NMOSD‐ON from ION with only moderate diagnostic accuracy.